Intestinal inflammation in nursing infants: different causes and a singletreatment... but of protected origin - Pancaldi, M.; Mariotti, I.; Balli, F. (Acta Biomedica Atenei Parmensis, 2009)
Three case histories of nursing infants suffering from different forms of intestinal problems, who underwent special dietary therapy in order to solve situations that would be difficult to deal with using the special artificial milk varieties on the market, are presented. These children were administered a homemade food consisting of Parmigiano Reggiano cheese seasoned for at least 36 months, rice or maize custard and tapioca, sugar, maize oil. In the first case the diagnosis of “widespread nonspecific acute colitis” was made compatible with “antibiotic-associated colitis” and Clostridium difficile was isolated from the feces.The second case, under the suspicion of cow’s milk allergy, was fed by soya and hydrolyzed milk with persitent disturbed alvus with greenish feces and mucus. The third case was represented by a nursing child with persistent diarrhoic alvus after an acute episode with subsequent intolerance to rice milk. After the introduction of the food based on Parmigiano Reggiano cheese, all cases showed a rapid and progressive improvement of symptoms and alvus characteristics and were discharged with increased weight. The Parmigiano Reggiano cheese shows a high concentration of easily absorbed amino acids and oligopeptides like a hydrolyzed proteic preparation. As regards the lipoid component the medium and short chain fatty acids  are directly absorbed in the bowel and immediately usable as a significant source of energy. Finally, another relevant characteristic of Parmigiano Reggiano cheese is the complete absence of lactose. The use of Parmigiano Reggiano cheese as a dietary therapy is appropriate not  only  for its high nutritional value, but also for its characteristics as a functional food that produces beneficial effects on health  with regards to the gastrointestinal tract and the inflammatory problems resulting from alimentary intolerance, post-therapeutic antibiotic dismicrobism, or post-infective conditions. Moreover, its efficay on these pathologic conditions is further improved by the prebiotic and probiotic effects resulting from the oligosaccharides and the bacterial flora of this natural food product, only derived from the nature and the work of skilled artisans closely tied to tradition.